Corrosion behaviour of mild steel in 1-alkyl-3-methylimidazolium tricyanomethanide ionic liquids for CO2 capture applications - Molchan, I.S.; Thompson, G.E.; Lindsay, R.; Skeldon, P.; V. Likodimos; Romanos, G.E.; P. Falaras; Adamova, G.; Iliev, B.; Schubert, T.J.S. (RSC Advances, 2014)
{The corrosion behaviour of mild steel (MS) was systematically investigated as a function of the alkyl chain length in the cation of 1-alkyl-3- methylimidazolium tricyanomethanide ([Cnmim]TCM